Democracy, corruption and civil liberties: does national context influence corporate carbon disclosure? - Pinheiro, Alan Bandeira; Sampaio , Thicia Stela Lima; Rodrigues , Rubens Carlos; Batistella , Ana Julia (Revista de Administração da UFSM, 2022)
Design/methodology/approach: This research analyzes the carbon disclosure of 1328 companies based in 19 countries. The level of democracy, corruption and civil liberties in the countries was measured using variables from the Varieties of Democracy database. The data were analyzed using three econometric models. Purpose: This research paper answers the following question: How does the country level of democracy, corruption and civil liberties affect carbon disclosure? Findings: The results show that the carbon disclosure of companies is affected by the institutional context of the country where the company operates. Therefore, in countries where the level of democracy and control of corruption is higher, companies are more involved in carbon disclosure. Research limitations/implications: The findings confirm the Institutional Theory, by reinforcing that not only the organizational context, but also the social and political context of the country are relevant for the dissemination of carbon. Practical implications: Managers of companies based in countries with a greater voice for citizens and a lower level of corruption should invest more resources for the dissemination of carbon. In these countries, companies are under greater pressure from stakeholders for information on carbon emissions. Social implications: The findings show that policy makers can incorporate protection mechanisms for stakeholders and not just shareholders. Lawmakers can propose increased penalties and criminalized corrupt practices and illicit enrichment of public officials. Less power of voice for citizens and a higher level of corruption can reduce the effectiveness of national policies for sustainable development. Originality/value: This research, in addition to advancing the studies on carbon disclosure in different national contexts, has for the first time used the credit rating control variable.